Design of high-frequency transformer for high current DC power supply - Sum, Zong Wei (2019)
The design of a High-Frequency Transformer for High Current DC power supply has great significance and importance. This report will include a research concept of DC-DC converter working principle, and the research of transformer core selections, the selection of transformer specifications, material selections, high-frequency transformer calculations, Autodesk Inventor software design, and ANSYS Electronics Desktop Maxwell design with simulations.